Begal Anak; Pemenuhan Hak dan Lembaga Pembinaan Khusus Anak Kelas II A Bandar Lampung - Eka Intan Putri (Universitas Lampung, 2019)
Child protection is all activities to ensure the implementation of the guaranteed rights of children, including the rights of children as criminals. Legalization is a crime and deviation in society that also violates social norms, wherever and done by anyone. It is often heard that there are still complaints from families and convicted children regarding alleged violations of the implementation of the rights of criminal child rights in the